Immune checkpoint inhibitors in gynecologic cancers with lessons learned from non-gynecologic cancers. (2nd August 2016) - Menderes, Gulden; Hicks, Christopher; Black, Jonathan D.; Schwab, Carlton L.; Santin, Alessandro D.
ABSTRACT: Introduction : The immune system plays a critical role in controlling cancer through a dynamic relationship with cancer cells. Immunotherapy can establish a sustained immune response against recurring cancer cells leading to long-term remissions for cancer patients. The use of immune checkpoint inhibitors, which work by targeting molecules that regulate immune responses, might be a promising avenue of immunotherapeutic research in gynecologic cancers. Areas covered : This review focuses on the use of immune checkpoint inhibitors targeting cytotoxic T lymphocyte antigen-4 (CTLA-4) and the programmed death receptors such as PD-1 and PD1-ligand in gynecologic cancers. Combinatorial approaches utilizing immunotherapeutic agents with conventional treatments as well as immune-related response criteria and the adverse effects arising due to checkpoint inhibitor immunotherapy have been also discussed in the review. Expert opinion : After years of very little success, a better understanding of the pivotal role of the tumor microenvironment in suppressing anticancer immunity and the exploration of treatment regimens using immune checkpoint inhibitors alone or in combination have finally led to the development of effective cancer immunotherapies and to improve survival of patients with certain types of advanced cancers. While the clinical experience with immune checkpoint inhibitors in gynecologic cancer patients remains limited, early signal of clinical activity strongly suggest that immunotherapy will play a significant role in the year to come in at least a subset of gynecologic cancer patients.